Understanding Consumer Perceptions And Attitudes Towards The Implementation Of Augmented Reality Marketing For High Involvement Products - Ni Made Dewi Putri Maharani (Green Publisher Indonesia, 2024)
Augmented Reality (AR) enhances an individual's perception of reality by adding digital elements to the physical world. Augmented Reality Marketing (ARM) occurs when AR is used to support branding or sales. This research aims to bridge the gap in the literature regarding ARM, particularly in the context of High Involvement Products (HIP). Through interviews and observations, this study highlights consumer views on ARM in the context of HIP. The results show that consumers see ARM as a valuable tool that provides informative and emotional benefits, increasing their interest in purchasing HIP. However, ARM is not seen as a replacement for other sources of information but rather as a complement. Despite being perceived as time-consuming and difficult to use, ARM has great potential as a standard practice in the future. Consumers find ARM especially useful when product design is a primary focus in the purchase decision. Therefore, the application of ARM may not be essential for all companies, as its main advantage lies in its ability to visualize products in real-life situations before purchase.